1992
DOI: 10.1103/physreva.45.3041
|View full text |Cite
|
Sign up to set email alerts
|

Role of the ponderomotive energy in two-color photodetachment of an ion

Abstract: We study, within a time-independent framework, the photodetachment of an ion by a weak highfrequency field in the presence of a field of low frequency al. . We explore the role played by the ponderomotive energy Prdue . to the low-frequency (LF) field. If Pi~hurt" the threshold energy for photodetachment by the high-frequency field is increased by the amount Pl. , while if PI.~hu& the threshold energy is decrea8ed, due to tunneling through the barrier formed by the atomic potential and the LF field. If P& & h~… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The only additional work needed for a specific system is to identify all the possible closed classical orbits. We note that an experiment has been done for the photodetachment of negative chlorine ions in a microwave field [28,29], and several theoretical studies have also been reported [29][30][31]. However, all of the previous time-dependent treatments assumed the applied field varied slowly enough that the electron was driven by a constant electric field during each detachment event, which approximately corresponds to the situation in the reported experiment [28,29].…”
Section: Introductionmentioning
confidence: 91%
“…The only additional work needed for a specific system is to identify all the possible closed classical orbits. We note that an experiment has been done for the photodetachment of negative chlorine ions in a microwave field [28,29], and several theoretical studies have also been reported [29][30][31]. However, all of the previous time-dependent treatments assumed the applied field varied slowly enough that the electron was driven by a constant electric field during each detachment event, which approximately corresponds to the situation in the reported experiment [28,29].…”
Section: Introductionmentioning
confidence: 91%
“…In the regime characterized by 6/cuL ))1 it was not possible to make any connection between the threshold shift and the measured cross section [1,2]. The ripples found in the curve showing the cross section as a function of AH were interpreted [1 -3] in terms of interference of the direct photoelectron wave and the wave that rejects from the repulsive barrier formed by the LF field whose characteristic height was evaluated [3] to be 2b" in analogy with the explanation given in Ref. [4], where the photodetachment in the presence of a static electric field was studied.…”
mentioning
confidence: 99%
“…are still dominated by the interference processes made evident by Eq. (3), which gives the transition amplitude. By further decreasing ET, a situation may be realized, see Fig.…”
mentioning
confidence: 99%